Impact of Rural Ageing on Non-Grain Agricultural Production in China: An Analysis Based on Food Security Strategy - Yuanzhi Guo; Yuan Tian (Foods)
The increasing population ageing in rural China has had a far-reaching impact on agricultural production structures. However, most of the existing studies on the impact of rural ageing on NGAP are based on a micro-farmer perspective and lack consideration under macro policies. This study analyses the impact of rural ageing on NGAP within the framework of food security strategy and examines this relationship using provincial panel data based on revealing the spatial-temporal characteristics of the two. The results show that the ageing level in rural China from 2005 to 2021 exhibited a rapidly rising trend and an unbalanced distribution pattern with decreasing spatial agglomeration, while the evolution of NGAP followed an upward and then downward trend, with an increasing degree of spatial agglomeration. Under the food security strategy, rural ageing has a significant dampening effect on NGAP, which mainly stems from the partial mediating roles of the increase in the area of farmland per labourer and agricultural-related fiscal investment. In light of the future trend of population ageing in rural China, targeted measures are needed to stabilize grain production and guarantee national food security.